Significance of pretransplant and de novo anti-HLA antibody detection after simultaneous pancreas-kidney transplantation - I. V. Dmitriev; N. V. Borovkova; S. P. Shchelykalina; N. V. Doronina; N. S. Zhuravel; A. V. Pinchuk (Трансплантология (Москва))
Introduction. Nowadays, there are few studies concerning assessment of the clinical significance of determining the level of pretransplant and de novo anti-HLA antibodies in patients after simultaneous pancreas-kidney transplantation.Aim. The study of the incidence, timing of formation and specificity of pretransplant and de novo anti-HLA antibodies in patients after simultaneous pancreas-kidney transplantation.Material and methods. We conducted a prospective and retrospective research to study the incidence, timing of formation and specificity of pretransplant and de novo anti-HLA antibodies in 55 patients after simultaneous pancreas-kidney transplantation performed at the N.V. Sklifosovsky Research Institute for Emergency Medicine from 2008 to 2022.Results. There were 4 patients with preformed anti-HLA antibodies (7%). The formation of de novo anti-HLA antibodies after simultaneous pancreas-kidney transplantation was observed in 17 patients (31%). There were 5 patients with antiHLA class I, 3 patients with anti-HLA class II, 3 patients with anti-HLA class I and II, 5 patients with anti-MICA and 1 patient with both classes of anti-HLA and anti-MICA. The formation of de novo anti-HLA antibodies significantly increased the incidence of acute rejection (47% compared with 13%, p=0.014).Conclusion. The frequency of pretransplant and de novo anti-HLA antibody detection in the recipients at our Center is comparable to published data from other transplant centers. We obtained evidence that the formation of de novo antiHLA antibodies increases the incidence of acute rejection after simultaneous pancreas-kidney transplantation.